The self-attitude of parents raising children with special needs - Y.V. Borisenko; A.A. Semenichheva (Экспериментальная психология)
Context and relevance. We studied the peculiarities of the self-attitude of fathers and mothers of one or more children with special needs. All the participants are Russian-speaking men and women, residents of Russia. Objective. The goal of our study was to study the peculiarities of the self-attitude of parents raising children with special needs. Hypothesis. The parent's self-attitude is related to the presence of health features of his child (children). Methods and materials. The study involved respondents (N=180) aged 28 to 45 years (M=36.3; SD=4.80), of which 50% were female. Also there were 50% of parents raising children with special needs. The following instruments were used: V.V. Boyko's method of diagnosing the type of emotional reaction to environmental stimuli, V.V. Stolin's self-attitude questionnaire, S.R. Pantileev and D. A. Leontiev's Purpuse in life test. Results. Parents of children with special needs have gender specificity in indicators of global self-attitude, indicators of interest in their personality, self-guidance, and consistency in their actions and deeds, self-accusation, as well as self-understanding are higher than those of parents of healthy children. Conclusions. Parents of children with special needs tend to expect others to have a negative attitude towards them, and are insecure about themselves, they tend to give a negative meaning to environmental stimuli and focus their attention on experiences.